Selection ways of rowers in kayak and canoe based on anthropometric iIndicators - Rustamovich, K. U.; Fatullobekovich, U. F. (Web of Synergy: International Interdisciplinary Research Journal, 2023)
Before this article, we paid attention to the anthropometric indicators as well as the functional indicators of rowers aged 13-14 years. Using the Skibinsky index, we determined the functional indicators of rowers in the experimental and control groups.